Evaluation Of HR Planning And Hiring Performance: A Quantitative Measurement Model For Talent Management Optimization - Andrian, Danny; Kurniawati, Era Tri Suci; Rahmadilla, Ade; Valani, Silvia; Aima, Havidz (Amirul Bangun Bangsa Publishing, 2025)
This study developed a quantitative measurement model to evaluate the performance of human resource planning and recruitment using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The research involved 30 organizations that implemented a structured planning and hiring system. The results showed a strong correlation between workforce strategic planning and talent suitability index (β = 0.456, p < 0.001), with the effectiveness of the recruitment process having a significant effect on talent retention scores (β = 0.389, p < 0.001). The measurement model showed excellent psychometric properties with an Average Variance Extracted value ranging from 0.712-0.847 and a Composite Reliability score between 0.891-0.934. The R-square value for endogenous constructs ranges from 0.743-0.891, indicating superior predictive capabilities. The developed framework provides a comprehensive evaluation instrument to optimize talent management strategies through an integrated assessment of the effectiveness of recruitment planning and outcomes.